Вплив електрострумової обробки розплаву алюмінієвого сплаву В95пч на механічні властивості та структуру литого стану з урахуванням додаткової термічної обробки - Kim, Kyung-Hyun; Suk, Sim Hyun; Цуркін, В.М.; Іванов, А.В.; Жданов, О.О.; Гумененко, М.К.; Честних, М.В.; Дьогтєв, Ю.Н. (Physico-technological Institute of Metals and Alloys, 2023)
The paper presents the results of investigation of pulse electric current treatment of liquid state of Al-Zn-Mg-Cu alloy of B95пч modification in complex with (AlTi5B1 and NaCl) reagent treatment in order to determine the conditions and exposure parameters under which the level of mechanical properties that correspond to indices of cast alloy after thermal treatment is achieved. As is known, alloys of Al-Zn-Mg-Cu system are widely used in mechanical engineering and aircraft construction. In this case, the performance properties of the pieces of machinery produced of these alloys must be ensured at the highest level. For this purpose, after casting operations the heat treatment is used that increases significantly the price of the finished billets. That is why the urgent task arises of searching for methods of alloy treatment at the casting stage, which would provide the indices of mechanical properties of Al-Zn-Mg-Cu system cast alloy at the level that would meet the result of heat treatment. The studies presented in this paper have shown the principle possibility of achieving this goal. According to mentioned results it is proposed to use for treatment the pulses electric current in complex with reagents treatment. If reagent treatment acts on the elements of the alloy structure selectively, then energy processing forms a complex of phenomena that provide an active improvement of the cast alloy quality. It is proved that for application of electric current treatment, it is necessary to immerse the electrodes with an insulated side surface to the different depth and introduce the optimal dose of electric energy density of the order of 108 J/m3. The suggested principle of melt treatment provides practically rounded shape of a-Al grains and an increase of casting microstructure homogeneity degree. Strength indexes (σв, σ0.2) are raised by 2.3 times, that practically corresponds to the result of heat treatment according to T6 procedure. This result can be explained by the complex action on the melt of energy and reagent influence that changes the mechanisms of structure formation and solidification, inter alia through the active homogenization and degassing of metal liquids while increasing the crystallization centers, providing the formation of cast metal substructure with a more “advantageous” solid solution morphology based on Al and eutectic components that usually occurs at alloys of the Al-Zn-Mg-Cu system during quenching.